Defining best practices in sustainable urban regeneration projects - Castanheira, Guilherme (2013)
This paper aims at analysing three international sustainable urban regeneration projects. The analysis is based in the application of ten urban sustainability indicators from two sustainability assessment tools (Sustainable Building Tool for Urban Planning in Portugal - SBToolPT-UP and International Sustainable Building Tool for Urban Planning– SBTool Urban) that are being developed at national and international level, respectively. Through this analysis it is intend to define the best practices for sustainable urban design, which allows to define the benchmarks of both tools and to support designers in the processes of decision making which goal is to optimize the sustainability of new or regenerated urban areas.